Puccinia marrubii (Pucciniaceae), a new rust species on Marrubium globosum subsp. globosum from Niğde and Malatya in Turkey - Kabaktepe, Şanli; Mutlu Bi̇rol; Karakuş, Şükrü; Akata, Ilgaz (Phytotaxa, 2016)
A new species of rust fungus, Puccinia marrubii sp. nov. is described from Turkey. The new species is the first Puccinia species to be identified on genus Marrubium (Lamiaceae). In order to determine the phylogenetic relationships of the new species, ITS region was amplified by PCR, sequenced, and analyzed. In addition to the ITS region of seven Puccinia species, P. annularis, P. jasmini, P. malvacearum, P. nigrescens, P. phlomidis, P. salviae, and P. serpylli were sequenced for the first time. Phylogenetic analyses performed by using distance, Bayesian methods confirmed that the new rust was closely related to P. serpylli, P. malvacearum, P. salviae, and P. annularis. The diagnostic morphological characteristics of the new species were discussed with the phylogenetically related species.